Diagnosis of research data management in teachers and researchers of the Universidad Central “Marta Abreu” de Las Villas - Machado Rivero, Manuel Osvaldo; Batista, Dianelis Olivera; Placeres, Grizly Meneses; Peralta González, María Josefa; Vancauwenbergh, Sadia (Iberoamerican Journal of Science Measurement and Communication, 2024)
Objective. This study aimed to diagnose the practices related to research data management (RDM) at the Universidad Central “Marta Abreu” de Las Villas, Cuba. Methodology. This study employed a nonexperimental, descriptive, and cross-sectional design. An online questionnaire was administered to teachers and researchers. The instrument consisted of 42 questions grouped into five dimensions. Results. The sample consisted of 320 individuals, 4.06% of whom were researchers and 95.94% of whom were teachers. The majority of research was conducted within the fields of social sciences (45%), followed by natural sciences (20.94%) and engineering (19.69%). Over 60% of the data generated in the research were digital. Text documents (94.38%) and spreadsheets (55%) were the most commonly used data formats. The mean annual storage capacity was 44.06%, with a minimum of 50 GB. Personal computers, universal serial bus sticks, and other storage devices were the most common forms of data storage. In at least one instance, 54.69% of respondents indicated they had experienced data loss. A majority (69.06%) of respondents indicated that they would prefer the university to retain at least some of their data. Email was identified as the primary data exchange method (72.81%). Conclusions. Best practices for managing research data were not followed, limiting their preservation, socialization, and impact. There was no institutional policy for managing these data. However, teachers and researchers expressed interest in developing a culture of RDM.